COMUNICAÇÃO INSTITUCIONAL E UNIVERSIDADE: diretrizes para a divulgação científica no estado de Mato Grosso - TEIXEIRA, DANIELLE TAVARES (2016)
The study aims to identify the initiatives of Science Divulgation undertaken by the Federal University of Mato Grosso (Universidade Federal do Mato Grosso - UFMT) and the University of the State of Mato Grosso (Universidade do Estado do Mato Grosso - Unemat), with goals to updating and improvement of institutional communication, increased interaction with interlocutors and strengthening of the state's image as a producer of Science, Technology and Innovation (Ciência, Tecnologia e Inovação - CT & I). Bibliographical and documentary researches, priority areas for scientific development and dissemination have been undertaken; interviews; image audit in the state media; diagnosis of the main scientific journalism products developed by UFMT and Unemat, as well as joint initiatives (Fapemat Ciência magazine and Rede de Dilvulgação Científica - Science Communication Network). The investigative method adopted can be characterized as Participant Observation, concieved in close association with problem solving, awareness taking or production of new knowledges (THIOLLENT, 1996, 1997). This strategy combines different techniques of social research, defined according to each stage of the investigation process. From the analysis of the scientific content published in state newspapers, it was possible to verify that these public Higher Education Institutions (HEI) do not occupy relevant place in such vehicles yet, which can be justified by the inadequacy of language or relationship channels, as well as by the necessity of a more efficient policy of divulgation. The mapping of the portals and institutional social media channels showed that the use of these vehicles can be better dynamized. Finally, the conclusions indicate that cultural and institutional differences between the two Higher Education Institutions make not viable the adoption of an integrated Policy of Scientific Communication, that is common between UFMT and Unemat. The development of actions for the dynamization of the divulgation of these institutions can be considered in the ambit of the State System of Science, Technology & Innovation.